Constructing a city liveability index and evaluating the spatial pattern of liveability of Guwahati city - Mahanta, Anwesha; Borgohain, Parijat (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction: Urbanization is a global phenomenon on the rise in recent decades. In this context, the concept of liveability has emerged as a fundamental instrument for assessing living standards in urban areas. Currently, cities are home to 55% of the world's population, and by 2050, that number is predicted to rise to 68%. The urbanization process has been more evident in developing countries of Asia, where a significant amount of the world's population growth is occurring. However, limited studies are exploring the liveability status of cities in developing countries and the spatial pattern of liveability across the city.The purpose of the article: The study intends to construct a city liveability index incorporating residents’ perspectives. The research also evaluates the liveability of different wards of the city and identifies the factors driving the spatial pattern of liveability across the city.Research Methods: A weighted sum methodology was used to calculate the city liveability index and weights for each indicator were determined using Principal Component Analysis (PCA). The indicators are determined through residents’ perspective and a primary survey was carried out to identify and rank the key indicators of liveability.Main findings: In the current research, it can be observed that wards located at the undulating topography have been mostly identified as low-liveable or very low-liveable wards. City growth is hampered by undulating topography because of higher expenses and challenges in infrastructural development, restrictions on land use, difficulty in road construction and the risk of landslide or erosion. The land use, distribution of amenities and spatial structure of the city is also greatly influenced by the transportation network system, which determines the movement of people and goods in the metropolitan areas. In the current context, the location of Guwahati-Shillong Road connecting the core of the city with south eastern region has been vital to the development of this part of the area.Scientific novelty and practical implication: The research for the first time attempts to construct a city liveability index incorporating indicators based on residents' definition of liveability in Guwahati city. The findings will assist the authorities and policymakers in formulating policies emphasizing the development of low-liveable wards. Moreover, the study recommends constructing strong road connectivity which contributes towards the growth of city facilities and services in least developed wards enhancing the overall liveability of the city.